2012
DOI: 10.1080/10810730.2011.635768
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Thematic Condom Advertising Campaign on Condom Use in Urban Pakistan

Abstract: This study aims to assess communication processes involving a thematic condom advertising campaign in Pakistan in 2009. To evaluate the social marketing campaign for Touch condoms, the authors conducted a nationally representative survey of 1,606 men married to women aged 15-49 years. About 15% of urban married men were aware of Touch advertising. After controlling for a range of other variables including daily television viewership, confirmed awareness of Touch advertising was associated with a higher level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
0
9
1
Order By: Relevance
“…This study provides some insight regarding how long the impact of a condom-advertising campaign may last. Although an earlier study found that exposure to the first phase of the Touch campaign (implemented in February and March 2009) was associated with higher condom use in the three-week period immediately following that campaign (Agha and Beaudoin 2009), this study shows that exposure to the first phase of the Touch campaign was not associated with improvements in behavior observed five months later (that is, at the time of the follow-up survey). The (lack of) effect of exposure to the first phase of the Touch campaign on behavior observed five months later was tested without including in the equation the variable measuring exposure to the second phase of the campaign (not shown).…”
Section: Discussioncontrasting
confidence: 82%
“…This study provides some insight regarding how long the impact of a condom-advertising campaign may last. Although an earlier study found that exposure to the first phase of the Touch campaign (implemented in February and March 2009) was associated with higher condom use in the three-week period immediately following that campaign (Agha and Beaudoin 2009), this study shows that exposure to the first phase of the Touch campaign was not associated with improvements in behavior observed five months later (that is, at the time of the follow-up survey). The (lack of) effect of exposure to the first phase of the Touch campaign on behavior observed five months later was tested without including in the equation the variable measuring exposure to the second phase of the campaign (not shown).…”
Section: Discussioncontrasting
confidence: 82%
“…For the most part, the campaigns were general family planning/birth spacing campaigns that aimed to increase uptake of modern contraceptive methods and services among men and women of reproductive age. Often campaigns targeted specific sub-groups including women (72%), men (63%), married people (28%), people of low (Bailey, Janowitz, Solis, Machuca, & Sauzo, 1989; Kincaid et al, 1996 ; Singhal & Rogers, 1999 ), middle (Agha & Beaudoin, 2012 ; Agha & Meekers, 2010 ), or high (Foreit, de Castro, & Duarte Franco, 1989 ) socioeconomic status or people of urban (Agha & Beaudoin, 2012 ; Agha & Meekers, 2010 ; Babalola & Brown, 2001 ; Babalola, Vonrasek, Brown, & Traore, 2001) or rural (Singhal & Rogers, 1999 ; Sypher, McKinley, Ventsam, & Valdeaellano, 2002 ) residence. A few campaigns also targeted health workers (Basten, 2009 ; Boulay, Storey, & Sood, 2002 ; Kim, Kols, Nyakauru, Marangwanda, & Chibatamoto, 2001; Palmer & Sood, 2004 ; Shefner-Rogers & Sood, 2004 ), community leaders (Basten, 2009 ; Kim & Marangwanda, 1997 ), and religious authorities (Blake & Babalola, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of a few recent studies [ 18 , 19 ], there is a near-absence of assessments of the success or failure of strategies adopted to change family planning behavior in Pakistan. Much better understanding and documentation regarding the types of interventions that have had success in Pakistan is needed.…”
Section: Discussionmentioning
confidence: 99%